Impact of different anticoagulation management strategies on outcomes in atrial fibrillation: Dutch and Belgian results from the GARFIELD‐AF registry. (25th September 2020) - Seelig, Jaap; Hemels, Martin E. W.; Xhaët, Olivier; Bongaerts, Maarten C. M.; de Wolf, Axel; Groenemeijer, Björn E.; Heyse, Alex; Hoogslag, Pieter; Voet, Joeri; Herrman, Jean‐Paul R.; Vervoort, Geert; Hermans, Walter; et al.
Abstract: Background: The uptake rate of non–vitamin K oral anticoagulants (NOAC) for the treatment of non‐valvular atrial fibrillation (AF) was far lower in the Netherlands (NL) compared to Belgium (BE). Also, patients on VKA in NL were treated with a higher target international normalized ratio (INR) range of 2.5 to 3.5. Objectives: To explore the effect of these differences on thromboembolism (TE) and bleeding. Methods: Data from the GARFIELD‐AF registry was used. Patients with new‐onset AF and ≥1 investigator‐determined risk factor for stroke were included between 2010 and 2016. Event rates from 2 years of follow‐up were used. Results: In NL and BE, 1186 and 1705 patients were included, respectively. Female sex (42.3% vs 42.2%), mean age (70.7 vs 71.3 years), CHA2 DS2 ‐VASc (3.1 vs 3.1), and HAS‐BLED score (1.4 vs 1.5) were comparable between NL and BE. At diagnosis in NL vs BE, 72.1% vs 14.6% received vitamin K antagonists (VKA) and 17.8% vs 65.5% NOACs, varying greatly across cohorts. Mean INR was 2.9 (±1.0) and 2.4 (±1.0) in NL and BE, respectively. Event rates per 100 patient‐years in NL and BE, respectively, of all‐cause mortality (3.38 vs 3.90; hazard ratio [HR] 0.86, 95% confidence interval [CI] 0.65‐1.15), ischemic stroke/TE (0.82 vs 0.72; HR 1.14, 95% CI 0.62‐2.11), and major bleeding (2.06 vs 1.54; HR 1.33, 95% CI 0.89‐1.99) did not differ significantly. Conclusions: In GARFIELD‐AF, despite similar characteristics, patients on anticoagulants were treated differently in NL and BE. Although the rate of major bleeding was 33% higher in NL, variations in bleeding, mortality, and TE rates were not statistically significant.